THE EFFECTIVENESS OF NARRATIVE THERAPY IN REDUCING PERCEIVED STIGMA DISORDER AMONG ADOLESCENTS WHO COMMIT MISDEMEANORS WHO ARE PLACED IN THE OBSERVATION HOME IN JEDDAH CITY - Dr. Ali Abdulrahman Alshehri, Dr. Hadi Mohammed Alkhathami (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The current study aims at identifying the effectiveness of Storytelling therapy in reducing perceived stigma disorder among adolescents who commit misdemeanors and are placed in the Observation Home in Jeddah City. The sample of this study consisted of (30) adolescents who committed misdemeanors and had a low degree of stigma. The sample was intentionally chosen, and the sample was divided into two groups randomly with 15 adolescents per group; control and experimental group. The following instruments were used in the study: The Perceived Stigma Scale (developed by the two researchers), in addition to the narrative therapy program (developed by the researchers); which included (18) sessions, it took nearly two and a half months by two sessions per week, with a duration of 60 minutes per session. The results of the study indicated that there were statistically significant differences at the level of significance (0.05) between the mean scores of the members of the experimental and control groups in the post-measurement on the perceived stigma scale in favor of the members of the experimental group. Moreover, there were statistically significant differences at the significance level (0.05) between the mean scores of the experimental group members in the pre and post measurement on the perceived stigma scale in favor of the post measurement. Finally, there were no statistically significant differences at the significance level (0.05) between the mean scores of the experimental group members in the two pre and tracking measures on the perceived stigma scale. Overall, these results indicate the effectiveness of narrative therapy in reducing the perceived stigma among adolescents who commit misdemeanors